Use of artificial intelligence applications in the educational environment of the New Ukrainian school: from inquiries to practice - Vasylchenko, Liliya; Shatska, Nataliya (Educological discourse, 2026)
The article considers the current problems of using artificial intelligence technologies (hereinafter AI) in the educational environment of the New Ukrainian School in the context of digital transformation. The relevance of the study is due to the rapid development of AI and the growth of requirements for the digital competence of teachers. The regulatory and legal support for the use of AI in general secondary education institutions of Ukraine, which is at the stage of formation and requires methodical understanding, is analyzed. Approaches to defining the essence of AI are summarized and its role as a tool for personalizing learning, supporting pedagogical decisions and automating educational processes is substantiated. At the same time, attention is focused on the risks associated with academic integrity, data security and ethical aspects. The results of domestic and foreign studies of the integration of AI into education are analyzed. Key areas are identified: the development of a digital educational environment, the use of intelligent systems, teacher training and the formation of their digital competence. The empirical basis is the results of a survey of teachers in the Zaporizhia region (2025). A high interest in AI as a direction of professional development was established and the industry specifics of its use were determined: in natural science education - for modeling and calculations, in language and literature, for creating content and analyzing texts. The main barriers were identified: lack of practical skills, methodological recommendations, limited time and concern about ethical issues. The phenomenon of cognitive overload was also recorded. The scientific novelty of the study lies in identifying regional features of teachers’ educational requests regarding the use of artificial intelligence, establishing industry specifics of the application of AI in the language and literature and natural science education, as well as in identifying new trends, in particular, the combination of a high level of interest with signs of cognitive overload and an increase in the demand for practical skills. The theoretical significance of the work lies in clarifying approaches to understanding the role of AI in the educational process and substantiating the need for its integration on the basis of pedagogical expediency, ethics and responsibility. The practical significance of the study lies in the possibility of using its results to develop advanced training programs for teaching staff, improving the content of postgraduate education, and creating methodological recommendations for the effective use of AI in teaching. Prospects for further research are related to the development of models for the systemic integration of AI into the educational process, the creation of practical recommendations for teachers of various educational fields, comparing data with other regions of Ukraine, and studying the impact of AI on the learning outcomes of education seekers.